THE WORD, PHRASE, AND SENTENCE PRODUCTIVITY, AND THE AVERAGE LENGTH OF UTTERANCES AMONG CHILDREN WITH MILD MENTAL RETARDATION - Astuty, Astuty; Rustono, Rustono; Su’udi, Edi Astini; Mulyani, Mimi (The Journal of Educational Development, 2017)
Children with mild mental retardation hereinafter referred to as CMMR experience cognitive impairment so that a variety of linguistic deficit exists. Nevertheless, their language skills can be optimized because within their inner language ability there is a Zone of Proximal Development (ZPD). This study aims to describe and explain the patterns of words, phrases, sentences, and the average length of utterances in the CMMR speech based on the minimum and maximum ability. This research approach is a qualitative one that is observationally controlled through a cross-sectional design. In this study, the researcher positioned herself as a key instrument because she acts as a human instrument that serves to fix the research focus, data sources, data collection, data reduction, and data presentation, and to draw conclusions/verification of the findings. The research data were in the form of written stories, conversations, and records of field data. The background the research was SLB Negeri Ungaran Semarang. The source of the data was the MMRC of Year 5. The technique of collecting data was recording and observation. The data were validated using data triangulation. Data analysis included (1) data reduction, (2) data presentation, and (3) inference or verification of the results. The findings of this study were as follows. (1) Based on the maximum capability, the word productivity was that the noun increased by 86%, the verbs by 81%, function words by 75%, adjectives by 76%, pronouns by 78%, numerals by 83%, and adverbs by 75%. (2) Based on the maximum capacity, the productivity of phrases was that the prepositional phrases increased by 72%, nominal phrases by 88%, verbal phrases by 70%, numeral phrases by 76%, pronominal phrases by 50%, conjunctive phrases by 100%, and adverbial phrases by 100%. (3) Based on the number of clauses related to the minimal capabilities, the sentence productivity found in the form of a simple sentences and can not be found in neither compound nor complex sentences and based on the maximum capabilities productivity of simple sentence increased by 86% and it was found that there was neither compound nor complex sentences. Based on the completeness of the sentence elements, it was found that according to the minimal ability there were 15% of complete sentences and 85% of incomplete sentences and based on the maximum capabilities, there was a 25% increase of complete sentences and a decrease by 75% of incomplete sentences. (4) Based the minimum capability, the average length of utterances (ALU) was 5.69 and based on the maximum capacity it increased by 6.24.